2020
DOI: 10.1002/agj2.20340
|View full text |Cite
|
Sign up to set email alerts
|

Do diverse cover crop mixtures perform better than monocultures? A systematic review

Abstract: Multi-species cover crop mixtures have been increasing in popularity. It has been hypothesized these mixtures produce more biomass, suppress more weeds, scavenge more N, conserve more soil water, stimulate more soil biology, promote higher yields of subsequent crops, and have higher production stability than the best of their monoculture counterparts. This systematic review synthesizes a growing body of cover crop mixture research to assess, for these metrics, whether cover crop mixtures can perform better tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 132 publications
(140 reference statements)
4
46
0
2
Order By: Relevance
“…However, weed management studies have shown that mixture performs better when composed of highly competitive species since biomass is a major predictor of weed suppression [133][134][135][136]. Furthermore, Florence and McGuire [137] performed a meta-analysis on 27 studies and found that mixture and monoculture cover crops perform comparably equal in seven metrics (biomass, N, weed, water, biology, yield, and stability). Time and method of cover crop termination can enhance, decrease or have no effect on weed establishment [138].…”
Section: Cover Cropsmentioning
confidence: 99%
“…However, weed management studies have shown that mixture performs better when composed of highly competitive species since biomass is a major predictor of weed suppression [133][134][135][136]. Furthermore, Florence and McGuire [137] performed a meta-analysis on 27 studies and found that mixture and monoculture cover crops perform comparably equal in seven metrics (biomass, N, weed, water, biology, yield, and stability). Time and method of cover crop termination can enhance, decrease or have no effect on weed establishment [138].…”
Section: Cover Cropsmentioning
confidence: 99%
“…Fornara & Tilman (2009) described the improvements in soil structure and health from increased soil organic matter, soil microorganisms and biological activities from increased plant diversity during decomposition. Then there is the decreased nutrient loss and increased soil water retention from increased plant diversity which increases crop productivity (Florence & McGuire, 2020) while simultaneously decreasing environmental contamination. Both diverse agronomic managements and cropping systems are key components of an integrated pest management system.…”
Section: Regenerative Agriculture: the Sustainable Transition Of Agricultural Practicesmentioning
confidence: 99%
“…The stability and beneficial ecosystem functions and services (e.g., regulation of weeds, pests or pathogens) of intensively managed agrosystems can be enhanced by increasing plant diversity through cover plants or associated crops. Increasing the cover crop species diversity is expected to enhance plant productivity through increased resource use efficiency [110]. Multispecies cropping agrosystems perform multiple functions and services other than crop production, increasing soil OM and C sequestration, regulating soil moisture, suppressing weeds, pathogens and pests, retaining N, sustaining higher soil biodiversity, etc.…”
Section: Effects Of Banana Cropping Systems On Nematodesmentioning
confidence: 99%